Agricultura de precisão no sudoeste do Paraná: processo de difusão, perspectivas e aspectos socioeconômicos - Montagna, Tainara Bruna (2021)
In the last decades, Brazilian agriculture has undergone major transformations throughout its production process. These changes were restructured, making the inclusion of technologies evident, resulting in a new technical, economic, and social model of agricultural development. Among the technologies, Precision Agriculture – PA stands out, which is configured as a tool to reduce costs, increase productivity and profits on the rural property. This work aimed to understand the process of Precision Agriculture development in the Southwest region of Paraná, which has spread rapidly, despite being characterized by family farming. For this, the methodological procedures were based on bibliographical review, collection, and analysis of secondary data, with systemic approach, technical visits, participation in sector events and application of questionnaires, which were fundamental to achieving the objective. The thesis was structured in five chapters, with the purpose of characterizing Precision Agriculture, presenting its tools and equipment with their respective functions and characteristics, demonstrating which are their development agents, that is, the factors that promote its development, exposing the profile of the AP adopter, highlighting the main tools used by them. In the first chapter, the modernization of agriculture process in Brazil and in the Southwest of Paraná was discussed. The second one sought to present a historical context of Precision Agriculture. In the third one, the existing Precision Agriculture equipment on the market and its main functions were surveyed. In the fourth chapter, the main agents that develop PA are presented, as well as the main mechanisms used by them for the diffusion process. In the last chapter, it was possible to trace the profile of PA adopters in terms of age, education, training courses and information sources used by them. The adoption of PA was also characterized in relation to the time of use, main tools adopted, ways of adopting the tools, land structure of the adopters and the main cultures that are used. Finally, the factors of adoption and diffusion of the AP were identified, as well as the analysis of the impacts on adoption. In addition, it was observed with this research that Precision Agriculture is defined as a high technology tool that provides a better crop management system, considering the variability present in agricultural areas, with the objective of optimizing production, reducing costs, and obtaining a better working condition, being disseminated by direct and indirect development agents, which expand its adoption.